2018
DOI: 10.1097/shk.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

HDL Cholesterol Efflux is Impaired in Older Patients with Early Sepsis: A Subanalysis of a Prospective Pilot Study

Abstract: Cholesterol efflux capacity seems to be significantly impaired in sepsis patients who also exhibited a higher index of Dys-HDL. The findings suggest that HDL function may be impaired in older individuals with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…It does not take into account hepatic SR-BI receptor activity or expression or cholesterol ester transfer protein-mediated hepatic cholesterol transfer that are necessary for the entire process. [ 25 ] Zimetti and colleagues recently studied 59 patients with an acute phase response, of whom 37 had infections, and noted that APR patients had changes in HDL composition (specifically the displacement of ApoA-I by serum amyloid A) and reduction in cholesterol efflux (specifically due to decreased activity of SR-BI and ABCG1), going against this hypothesis. [ 26 ] Our study is different from Zimetti’s however, in that our population of severe sepsis and septic shock patients was critically ill as nearly all patients had multiple organ failure (SOFA score median 7, IQR 5–10), and the overall in-hospital and 28-day mortality were 20% and 31%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It does not take into account hepatic SR-BI receptor activity or expression or cholesterol ester transfer protein-mediated hepatic cholesterol transfer that are necessary for the entire process. [ 25 ] Zimetti and colleagues recently studied 59 patients with an acute phase response, of whom 37 had infections, and noted that APR patients had changes in HDL composition (specifically the displacement of ApoA-I by serum amyloid A) and reduction in cholesterol efflux (specifically due to decreased activity of SR-BI and ABCG1), going against this hypothesis. [ 26 ] Our study is different from Zimetti’s however, in that our population of severe sepsis and septic shock patients was critically ill as nearly all patients had multiple organ failure (SOFA score median 7, IQR 5–10), and the overall in-hospital and 28-day mortality were 20% and 31%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The cholesterol efflux assay is a quantitative assessment of HDL function and measures the ability of HDL to move lower density lipids from peripheral macrophages to the liver for clearance. HDL-mediated cellular cholesterol efflux assays will be performed to assess potential improvements in HDL function with LIE versus control as in previous studies 27. SOFA score assessment will occur prior to enrolment and 48 hours later as well as at 7 days to determine change in SOFA score over time as well as serum lactate.…”
Section: Methodsmentioning
confidence: 99%
“…Levels of very low-density lipoproteins and triglycerides increase due to adipose tissue lipolysis, which is stimulated by catecholamines, cortisol and growth hormone, possibly to meet energy needs or for bacterial toxin binding 8 24 25. Although some have attempted to demonstrate that these changes in cholesterol levels are not causal,26 there may be a direct association between cholesterol levels and poor outcomes, as both cholesterol levels and functional status are predictive of poor outcomes 22 27–29. The physiological rationale for the protective effects of cholesterol is strong, and thus we believe a pilot investigational study is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, de la Llera et al have shown that in twenty healthy adults, an endotoxemia induced by LPS (3 ng/kg) administrated as an intravenous bolus infusion led to a reduced capacity of HDLs to efflux cholesterol in vitro [72]. Interestingly, when comparing the 10 oldest septic patients to the ten oldest healthy subjects, the cholesterol efflux was significantly reduced in septic patients (24 ± 1.2%) compared to control subjects (31.5 ± 1.0%) [84].…”
Section: Hdl Function In Inflammatory Statementioning
confidence: 98%